2022
DOI: 10.3390/nu14050950
|View full text |Cite
|
Sign up to set email alerts
|

Global Burden of Vitamin A Deficiency in 204 Countries and Territories from 1990–2019

Abstract: Vitamin A deficiency (VAD) is one of the important public health issues worldwide. However, a detailed understanding of the incidence and disability-adjusted life years (DALYs) due to VAD in recent years is lacking. We aimed to estimate the incidence and DALYs of VAD at global, regional, and national levels in terms of sex, age, and socio-demographic index (SDI). Using data from the 2019 Global Burden of Disease (GBD) study, the estimated annual percentage change (EAPC) was measured to assess trends in the age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 42 publications
(49 reference statements)
0
13
0
Order By: Relevance
“…In the GBD 2019 study, which utilised 46 data sources, a global age standardised prevalence of VAD was estimated to be 7.0%, accounting for 23.1 million cases. The highest prevalence rates were indicated in Central and Eastern sub-Saharan Africa, with rates of 25.9% and 23.5%, respectively [8,19,20]. It is important to note that these significantly lower estimates in GBD 2019 may have been influenced by various factors, such as data availability, model assumptions, analytical methods, and especially the case definitions employed, which were based on a combination of low serum retinol concentration (<0.7 μmol / l) and blindness and vision loss due to VAD.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In the GBD 2019 study, which utilised 46 data sources, a global age standardised prevalence of VAD was estimated to be 7.0%, accounting for 23.1 million cases. The highest prevalence rates were indicated in Central and Eastern sub-Saharan Africa, with rates of 25.9% and 23.5%, respectively [8,19,20]. It is important to note that these significantly lower estimates in GBD 2019 may have been influenced by various factors, such as data availability, model assumptions, analytical methods, and especially the case definitions employed, which were based on a combination of low serum retinol concentration (<0.7 μmol / l) and blindness and vision loss due to VAD.…”
Section: Discussionmentioning
confidence: 95%
“…The 2009 WHO report [4] and 2013 global study by Stevens et al [1] provide important information on the epidemiology of VAD, and the Institute for Health Metrics and Evaluation have continued to provide annual updates as part of the global burden of disease (GBD) project [7,8]. Despite these efforts, there is a need for continued understanding of the epidemiology of VAD in many LMICs in order to support many ongoing local and international efforts targeted at child malnutrition and VAD [9].…”
mentioning
confidence: 99%
“…Vitamin A deficiency, primarily caused by insufficient VA intake, is a 16 -EYE & ENT RESEARCH common public health issue worldwide [72]. Previous studies revealed that a low dietary intake of retinol equivalents is associated with an increased risk of glaucoma in Europeans [73], Africans [74], and Japanese Americans [75].…”
Section: Preliminary Exploration Of the Association Between Vitamin A...mentioning
confidence: 99%
“…Vitamin A (VA) is a generic term for a group of organic compounds that include retinol, retinal, retinoic acid, and provitamin A carotenoids. Vitamin A deficiency, primarily caused by insufficient VA intake, is a common public health issue worldwide [72]. Previous studies revealed that a low dietary intake of retinol equivalents is associated with an increased risk of glaucoma in Europeans [73], Africans [74], and Japanese Americans [75].…”
Section: Latest Updates Of the “Dual‐pressure Theory” Studymentioning
confidence: 99%
“…Vitamin A deficiency (VAD) is an issue of global public health concern, affecting about three billion people, mainly in developing countries, with a third of all those affected being children between 6 months and 5 years old ( https://data.unicef.org/topic/nutrition/vitamin-a-deficiency/# ), (Renaud et al 2013 ; Akhtar et al 2013 ; Zhao et al 2022 ). Vitamin A—a fat-soluble vitamin—plays a vital role in health functions such as improved cell division, immunity cell growth, differentiation of cells, development of embryos, and general growth (McLaren and Frigg 2001 ).…”
Section: Introductionmentioning
confidence: 99%